An analysis of the Regency of Rejang Lebong government policy in procuring the sports facility - Fadli Nugroho; Wawan Sundawan Suherman; Fitri Agung Nanda (Nicolaus Copernicus University in Toruń, 2020)
The Government Policy on the sports facility has been an important component in improving the achievement and the society interest toward the conduct of sports activities. With regards to the statement, the study aims at identifying the policy of the Regency of Rejang Lebong Government in terms of sports facility procurement. During the conduct of the study, the subjects that had been selected were: (1) the Head of the Regency of Rejang Lebong Youth and Sports Department, the Office of Culture, Tourism, Youth and Sports; (2) the Caretakers of the Regency of Rejang Lebong Indonesian National Sports Committee; (3) the Management of Rejang Lebong Sports Hall; (4) the Management of Munatirta Swimming Pool; (5) the Management of Outdoor Tennis Court; (6) the Management of the Indonesian Badminton Federation Indoor Badminton Court; and (7) the Management of Rejang Lebong Soccer Stadium. Then, the instruments that had been implemented in the conduct of the study consisted of: (1) document and archive study; (2) in-depth interview; and (3) observation on the procurement of the sports facility by the Regency of Rejang Lebong Government. As a result, automatically the nature of the study is descriptive qualitative research. Then, the results of the study show that the procurement of the sports facility, which covers planning, utilization and evaluation, has not been maximized yet. In the same time, it is also found that the policy made by the Regency of Rejang Lebong Government should highlight the sports facility procurement in order to support the achievement and also the society aspiration in performing sports activities.